STUDY OF ENHANCED OIL RECOVERY WITH ALKALINE SURFACTANT POLYMER INJECTION METHOD BY USING LABORATORY TEST - Edward ML Tobing; Hestuti Ani (Scientific Contributions Oil and Gas, 2014)
One effort to improve oil recovery in oil reservoirs after primary and secondary recovery period is to apply the method of Enhanced Oil Recovery (EOR). Screening of EOR on the characteristics of the reservoir rock and Àuid 'N' indicates that the suitable method is the injection of alkali surfactant polymer (ASP). This paper presents the results of laboratory tests to increase the oil recovery in the reservoir 'N' with ASP injection. The purpose of the laboratory testing was to determine the additional oil recovery by injecting a solution of ASP in the reservoir rock 'N'. Based on the results of compatibility, interfacial tension, rheology, thermal stability, filtration and static adsorption test on an ASP Àuid injection, the optimum concentration of each of the injection Àuid is obtained. Referring to the optimum concentration of the ASP, then the core Àooding test design based on a predetermined Àuid injection. The main result of the Àooding test cores showed an increase in oil recovery as much as 21.84% OOIP. When the results of the laboratory test was applied to the field scale by injecting Àuid into the reservoir ASP 'N', then the estimated potential increase in oil production as much as 11.457 million bbl.